2015
DOI: 10.1155/2015/927686
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide Mediates Depressive Effects Induced by Hydrogen Sulfide in Rostral Ventrolateral Medulla of Spontaneously Hypertensive Rats

Abstract: Hydrogen sulfide (H2S) plays a crucial role in the regulation of blood pressure and oxidative stress. In the present study, we tested the hypothesis that H2S exerts its cardiovascular effects by reducing oxidative stress via inhibition of NADPH oxidase activity in the rostral ventrolateral medulla (RVLM). We examined cell distributions of cystathionine-β-synthase (CBS) and effects of H2S on reactive oxygen species (ROS) and mean arterial blood pressure (MAP) in spontaneously hypertensive rats (SHRs). We found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 46 publications
(45 reference statements)
1
16
0
Order By: Relevance
“…It has been reported that H 2 S in the RVLM inhibits sympathetic vasomotor tone through opening K ATP channels [29, 30]. We have shown that H 2 S in RVLM suppressed the blood pressure in SHRs [14]. The signaling mechanisms in the CNS of the antihypertensive effect of H 2 S have not been elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been reported that H 2 S in the RVLM inhibits sympathetic vasomotor tone through opening K ATP channels [29, 30]. We have shown that H 2 S in RVLM suppressed the blood pressure in SHRs [14]. The signaling mechanisms in the CNS of the antihypertensive effect of H 2 S have not been elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…H 2 S is mainly produced endogenously by CBS and MST in the CNS [4, 5] and CBS is mainly expressed in the hippocampus and cerebellum, as well as the cerebral cortex and brain stem [8]. Our previous study has shown that CBS immunoreactivity was found in the rostral ventrolateral medulla (RVLM) neurons in vivo and the level of CBS proteins in the RVLM was lower in SHRs than in WKY rats [14]. In this study, our results showed that more than 80% of cultured medullary neurons were glutamate positive neurons, and CBS and MST were, respectively, expressed in these neurons in vitro, while the expression of CSE was negative in these primarily cultured medullary neurons.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations